Structural Compensation and Economic Value: How Traditional Agroforestry Systems Maintain Biodiversity in Sulawesi's Wallacea Hotspot - Hiola, Abdul samad (Jurnal Penelitian Kehutanan BONITA, 2025)
This study analyzed the trade-offs and synergies between economic productivity and biodiversity conservation across different land-use systems in Sulawesi, Indonesia. NMDS analysis revealed significant differentiation in species composition across systems (PERMANOVA, F=12.34, p<0.001). Natural forests were characterized by a high proportion of endemic species such as Agathis robusta, Molonggoile spp., and Biamenga spp., while agroforestry systems were dominated by economically valuable species such as Aleurites moluccanus (candlenut), Arenga pinnata (sugar palm), and Durio zibethinus (durian). Economic valuation revealed substantial differences in value per hectare: candlenut agroforestry (USD 2,115), sugar palm agroforestry (USD 1,785), durian agroforestry (USD 1,627), plantation forests (USD 895), and natural forests (USD 327). The analysis revealed a negative correlation between species richness and economic value (r=-0.87, p<0.05), but a positive correlation between tree density and economic value (r=0.79, p<0.05). Redundancy analysis identified basal area and tree density as the most influential vegetation structure parameters on species composition patterns (R²=0.68, p<0.001). The agroforestry system maintained basal area through higher densities of smaller trees, suggesting a structural compensation mechanism. These findings demonstrate that management intensification for economic species reduces species richness while maintaining structural parameters that support ecological functions. Structural compensation mechanisms in agroforestry provide an effective strategy for maintaining biodiversity in tropical landscapes under deforestation pressure, while highlighting the potential of an integrated approach to balancing conservation and sustainable development in the Wallacea hotspot.